Acid hydrolysis optimization of cocoa pod shell using response surface methodology approach toward ethanol production - Shet, Vinayaka B.; Sanil, Nisha; Bhat, Manasa; Naik, Manasa; Mascarenhas, Leah Natasha; Goveas, Louella Concepta; Rao, C. Vaman; Ujwal, P.; Sandesh, K.; Aparna, A. (Agriculture and Natural Resources, 2018)
Cocoa pod shell (CPS) is an underutilized agricultural lignocellulosic biomass. Hydrochloric acid (HCl) hydrolysis was carried out to release the reducing sugars from CPS. The conditions (CPS weight, concentration of HCl, revolutions per minute, hydrolysis period) which affect HCl hydrolysiswere screened using one factor at a time approach of which determined that CPS weight, HCl concentration and hydrolysis period had a significant effect on the acid hydrolysis process. The levels of these factors were further optimized using a central composite design using response surface methodology. The optimized conditionswere 8.36% (weight per volume) of CPS, 3.6 N of HCl concentration with 7.36 h of acid hydrolysiswhich yielded 4.09 g/L reducing sugars. A second order model was generated and validated, which was found to be a good fit (coefficient of determination = 0.914). The released reducing sugars after the acid hydrolysis under optimized conditions were subjected to alcoholic fermentation by Pichia stipitis to produce bioethanol. The bioethanol concentration reached 2 g/L at 2% (volume per volume) inoculum concentration after 72 h of fermentation.